The Relationship Between Pituitary Gland Dimensions, Thyroid Functions, and Seizure Activity in Patients with Epilepsy - Fettah Eren; Cihat Özgüncü; Ahmet Hakan Ekmekci (Archives of Epilepsy, 2022)

(untitled)
Objective:Morphological and functional changes in hormonal systems may present as the cause and/or result of epileptic seizures. The purpose of the present research is to evaluate the relationship between the structure of the pituitary gland, thyroid functions, and seizure activity in patients with epilepsy.Methods:It was designed as a hospital-based, retrospective, and case–control study. No secondary epilepsy patients (18-65 years) were included in the study. Disease duration, seizure frequency, and antiepileptic treatments were questioned. Electroencephalography findings were grouped as normal, nonspecific, slow wave activity, and epileptic activity. Seizure types were determined. The pituitary gland was measured with coronal T2-magnetic resonance imaging sequences. Pituitary gland width, height, and intercavernous distance were obtained. Thyroid-stimulating hormone, free triiodothyronine, and free thyroxine results were recorded.Results:There were 63 patients (mean age of 43.11 ± 12.38 years) and 44 healthy volunteers in the study. Pituitary gland width and intercavernous distance were lower in epilepsy patients compared to the control group (P = .012 and P = .006). Thyroid function test results were similar in the patient and control groups (P > .05). There was a negative correlation between the number of seizures in the last 1 month and the width of the pituitary gland (P = .008, r = −0.331). There was no relationship between other clinical features, antiepileptic therapy, and pituitary measurements and thyroid functions.Conclusion:The lower width of the pituitary gland and its relationship with the frequency of seizures support that seizure activity is associated with structural features of the hormonal system in patients with epilepsy.